Neuroanatomical mapping of huntingtin-associated protein 1 across the rostral and caudal clusters of mouse raphe nuclei and its immunohistochemical relationships with serotonin - Marya Afrin; Marya Afrin; Md Nabiul Islam; Mirza Mienur Meher; Mirza Mienur Meher; Mir Rubayet Jahan; Kanako Nozaki; Koh-hei Masumoto; Akie Yanai; Koh Shinoda; Koh Shinoda (Frontiers in Neuroanatomy)
Huntingtin-associated protein 1 (HAP1) is a crucial component of the stigmoid body (STB) and is recognized as a neuroprotective interactor with causative proteins for several neurodegenerative disorders (NDs). Due to HAP1 protectivity, brain regions rich in STB/HAP1 are typically shielded from neurodegeneration, whereas areas with little or no STB/HAP1 are often affected in NDs. Mounting evidence suggests that serotonin (5-HT) neuron dysfunction contributes to various NDs. While the raphe nuclei denote the origin of 5-HT neurons, HAP1 protectivity has yet to be determined there. To accomplish this, the present study evaluated the expression and detailed neuroanatomical distribution of HAP1 throughout the rostral and caudal clusters of raphe nuclei in adult mice brains and their morphological relationships with 5-HT by employing Western blotting and immunohistochemistry. Our results indicated that in the rostral cluster, HAP1-ir cells were extensively distributed across the caudal linear raphe, median raphe, dorsal raphe, supralemniscal raphe, caudal part of the dorsal raphe, pre-pontine and pontine raphe nuclei. In the caudal cluster, HAP1-ir neurons were disseminated throughout the raphe magnus, raphe obscurus, raphe pallidus, parapyramidal, and raphe interpositus nuclei. Our double-immunofluorescence labeling results confirmed that most of the 5-HT neurons contained HAP1 immunoreactivity throughout the rostral and caudal clusters of the raphe nuclei. These suggest that HAP1 is crucial for modulating/protecting serotonergic functions, plausibly by upholding 5-HT neuronal plasticity/integrity by raising the threshold for neurodegeneration. Our current findings might provide a fundamental basis for further research aimed at elucidating the role of STB/HAP1 in the pathophysiology of serotonin neurons.